MAXIMIZE NATURAL LIGHTING IN SIMPLE BUILDINGS WITH THE USE OF ROOF WINDOWS - Effendi, Ajeng Meila (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2023)
Abstract: Lighting is one of the utilities that must be fulfilled in a building. Based on the source, lighting is divided into two, namely natural lighting and artificial lighting. Natural lighting is lighting that comes from the sun. To find out the lighting standards that a room must have in Indonesia, we can look at the data in the Indonesian National Standard (SNI) 03-6197-2000. Meanwhile, measurements or simulations can be carried out using the Dialux Evo software. This study was conducted to determine the effect of roof windows on the lighting in a room in a simple building. This research was performed using the observation method with a quantitative research approach. The data obtained will be compared with the existing SNI for further evaluation. In a room with more or less lighting than SNI, a solution will be given to overcome it. Some of the answers are the use of roof windows for rooms that have lighting levels below SNI. Meanwhile, for rooms with a lighting level of more than SNI, a solution will be given in the form of using curtains to filter the incoming light. Keywords: Natural lighting, Dialux Evo, sunlight, roof windows